2008
DOI: 10.1105/tpc.108.063263
|View full text |Cite
|
Sign up to set email alerts
|

Functional Proteomics ofArabidopsis thalianaGuard Cells Uncovers New Stomatal Signaling Pathways

Abstract: We isolated a total of 3 3 10 8 guard cell protoplasts from 22,000 Arabidopsis thaliana plants and identified 1734 unique proteins using three complementary proteomic methods: protein spot identification from broad and narrow pH range twodimensional (2D) gels, and 2D liquid chromatography-matrix assisted laser desorption/ionization multidimensional protein identification technology. This extensive single-cell-type proteome includes 336 proteins not previously represented in transcriptome analyses of guard cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
264
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(283 citation statements)
references
References 118 publications
(136 reference statements)
17
264
1
1
Order By: Relevance
“…For this purpose, we focused on the line SDH14 and the wild type and hybridized RNA both from whole leaf and epidermal fragments. Evaluation of epidermal fragments has proven highly informative in assessing the transcriptome of guard cells (Leonhardt et al, 2004), while the proteome of guard cell protoplasts has also recently been studied (Zhao et al, 2008). However, our studies revealed no significant changes in the expression of genes in the succinate dehydrogenase antisense line compared with the wild type after adjusting for multiple testing, in keeping with the few significant changes reported for the fumarase antisense lines (Nunes-Nesi et al, 2007b).…”
Section: Analysis Of Alterations In Gene Expression In Illuminated Lesupporting
confidence: 51%
See 2 more Smart Citations
“…For this purpose, we focused on the line SDH14 and the wild type and hybridized RNA both from whole leaf and epidermal fragments. Evaluation of epidermal fragments has proven highly informative in assessing the transcriptome of guard cells (Leonhardt et al, 2004), while the proteome of guard cell protoplasts has also recently been studied (Zhao et al, 2008). However, our studies revealed no significant changes in the expression of genes in the succinate dehydrogenase antisense line compared with the wild type after adjusting for multiple testing, in keeping with the few significant changes reported for the fumarase antisense lines (Nunes-Nesi et al, 2007b).…”
Section: Analysis Of Alterations In Gene Expression In Illuminated Lesupporting
confidence: 51%
“…Moreover, analysis of the expression data did not uncover large changes in ABA-responsive genes (Hetherington and Quatrano, 1991;Hildmann et al, 1992;Abe et al, 1997) or of genes/proteins associated with ABA-mediated signal transduction relay (Leonhardt et al, 2004). The recent proteomic study of Zhao et al (2008) highlighted a plethora of proteins that were differentially expressed in guard cells as opposed to mesophyll cells, many of which have previously been characterized as being ABA responsive. Similarly, the experiments in which leaves from the transgenic and wild-type lines were incubated in the presence of the potassium channel blocker CsCl (Ichida et al, 1997) yielded similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we found that leptokurtic genes associated with guard cells are enriched in genes with recognized guard cell functions (Table 1): 28 out of 93 genes with known functions in guard cells (Zhao et al, 2008) are present in the list of 2345 guard cell leptokurtic genes (Fisher test, P < 6.3e-8.). Our analysis, based on the standardized transcriptome data set of normal Arabidopsis tissues, reveals that most of these genes are shared between guard cells and other tissues: Only three genes are guard cell specific (i.e., expressed above a basal level solely in guard cell samples), whereas the remaining 25 genes are shared between guard cells and other tissues.…”
Section: Experimental Analysis Of Leptokurtic Genes Associated With Gmentioning
confidence: 99%
“…In regulation of merging signals for ABA-and JA-triggered stomatal closures, guard cell abundant myrosinase THIOGLUCOSIDE GLUCO-HYDROLASE1 (TGG1) may have a role. tgg1 showed defects in ABA-inhibition of inward K + -channel activity and stomatal opening (Zhao et al, 2008) and ttg1 ttg2 produced reduced responses in the ABA-and JA-induced stomatal closures (Islam et al, 2009) suggesting a role of glucosinolate metabolism in the guard cell ABA signaling.…”
Section: Interaction Of Aba Signaling With Biotic Stress Response Patmentioning
confidence: 99%